Dynamics of Crude Palm Oil and Fresh Fruit Bunches Prices in the Era of Biodiesel Policy in Indonesia - Muhammad Farhan Kurniawan (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the dynamics of Crude Palm Oil prices and Fresh Fruit Bunches prices in the era of biodiesel policy in Indonesia. The study employs a quantitative approach using the Vector Error Correction Model method to examine both short-run and long-run relationships among Crude Palm Oil prices, Fresh Fruit Bunches prices, world oil prices, exchange rates, and biodiesel policy. The data used in this study consist of monthly time series data from 2021 to 2025 obtained from Statistics Indonesia, Bank Indonesia, the Palm Oil Plantation Fund Management Agency, and the World Bank Commodity Price Data. The results show that Crude Palm Oil prices and Fresh Fruit Bunches prices experienced significant fluctuations during the study period. The Johansen cointegration test indicates the existence of a long-run relationship among Crude Palm Oil prices, Fresh Fruit Bunches prices, world oil prices, exchange rates, and biodiesel policy. The implementation of biodiesel policy increased domestic demand for Crude Palm Oil, thereby affecting the dynamics of Indonesia’s palm oil market prices. In addition, Fresh Fruit Bunches prices tended to follow the movement of Crude Palm Oil prices, indicating the existence of a price transmission mechanism between the downstream and upstream sectors of the palm oil industry in Indonesia. This study also reveals that Indonesia’s palm oil market has become integrated with the global energy market, implying that changes in global energy prices and biodiesel policy can influence the stability of domestic palm oil commodity prices.